Producción de cinco variedades de café (Coffea) con la aplicación de tres bioestimulantes en el Centro Experimental Sacha Wiwa. - Calero Ramírez, Jasmín Estefanía (2023)
The project was carried out at Sacha Wiwa Experimental Center, in Guasaganda parish, La Maná canton, Cotopaxi province where the following objectives were set: To analyze the agronomic effect of coffee varieties with the application of biostimulants. To determine the coffee varieties with the highest production with the use of biostimulants. To establish the costs and income of the treatments under study. The factors under study were Factor A= five varieties of coffee: Cofenac-06, Cofenac-01, Napopayamino-2024, Cofenac-02, and Napopayamino- 3051; Factor B= Biostimulants: Inorganic Biostimulants and Organic Biostimulants and the Treatment of Control based on dolomite lime. The Completely Random Block Design (CRBD) was used with the application of Tukey's multiple range test at 5% statistical probability. The following variables were evaluated; plant height (m), stem diameter (mm), number of branches, production by coffee variety, production by biostimulant, production by treatment and economic analysis. As a main basis, a soil analysis was carried out that resulted in low % of organic matter, boron, ammonium, and sulfur. According to the textural type of the Loamy-Silty soil, the formulations of the Biostimulants were made in % urea, sulfur, chlorine, potassium, phosphorus, and lime dolomite with MO + NH4 + B to cover the requirements. The studied variable with the best response was achieved in the Cofenac-06 variety with the inorganic Biostimulant and the highest coffee production was obtained in the Napopayamino-2024 variety with 892.94 g; these two varieties are the most economically feasible based on the analysis of costs and income to cultivate.